2015
DOI: 10.1128/aem.02236-15
|View full text |Cite
|
Sign up to set email alerts
|

pH Tolerance in Freshwater Bacterioplankton: Trait Variation of the Community as Measured by Leucine Incorporation

Abstract: b pH is an important factor determining bacterial community composition in soil and water. We have directly determined the community tolerance (trait variation) to pH in communities from 22 lakes and streams ranging in pH from 4 to 9 using a growth-based method not relying on distinguishing between individual populations. The pH in the water samples was altered to up to 16 pH values, covering in situ pH ؎ 2.5 U, and the tolerance was assessed by measuring bacterial growth (Leu incorporation) instantaneously af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…This finding is consistent with reports of pH as the primary environmental predictor of microbial diversity in several ecosystems, both in New Zealand and globally (e.g. soil 5 , 36 , water 32 , 37 , alpine 38 , 39 ).…”
Section: Resultssupporting
confidence: 92%
“…This finding is consistent with reports of pH as the primary environmental predictor of microbial diversity in several ecosystems, both in New Zealand and globally (e.g. soil 5 , 36 , water 32 , 37 , alpine 38 , 39 ).…”
Section: Resultssupporting
confidence: 92%
“…This finding is consistent with reports of pH as the primary environmental predictor of microbial diversity in several ecosystems (e.g. soil 12 , freshwater 40 , alpine 38 ).…”
Section: Resultssupporting
confidence: 93%
“…These results showed that lowering the pH in RAS from pH 7 to pH 4 and maintaining it for three hours disrupted the function of the bacterial communities in the RAS+A and RAS-A as indicated by the deteriorated water quality following the stress application. Similarly, a study on bacterial communities in lakes and rivers found that a low pH was unfavorable for bacterial growth [ 21 ] and in soilless cultivation media, low pH resulted in a significant decrease of ammonia oxidation rates and ammonia oxidizing bacteria community diversity [ 22 ].…”
Section: Resultsmentioning
confidence: 99%